Correlation between human resouce plan and patient continuous care direction at Sibu Hospital - Khu, Fan Mei (Universiti Malaysia Sarawak (UNIMAS), 2012)
Sibu Hospital is a referral public hospital and leading teaching hospital which provides secondary and tertiary care to patients at Sibu Division and along the Rejang basin as well as Kapit, Sarikei, Mukah, Saratok and Bintulu. Population growth, related demographics and referral cases from 1 Malaysia clinics will increases the total demand of secondary and tertiary care in Sibu Hospital. Managing long-term supply and demand balance in specialty care environments is needed in quality of patient care. The end result of the human resource planning is therefore presented as work in progress because it is subject to further development of the required planning capacity and tools e.g. Human Resource Information System, further research and analysis to yield data required to refine the targets. A cross-sectional descriptive study carried out at the secondary services of specialist clinics from 1 January 2006 till 31 May 2013 at Sibu Hospital. A total of 44,790 patients from specialist clinics in the departments of Obstetrics & Gynecology and Pediatrics were selected into study.